Liposomes as a Putative Tool to Investigate NAADP Signaling in Vasculogenesis. Issue 11 (16th May 2017) - Di Nezza, Francesca; Zuccolo, Estella; Poletto, Valentina; Rosti, Vittorio; De Luca, Antonio; Moccia, Francesco; Guerra, Germano; Ambrosone, Luigi
ABSTRACT: Nicotinic acid adenine dinucleotide phosphate (NAADP) is the newest discovered intracellular second messengers, which is able to release Ca 2+ stored within endolysosomal (EL) vesicles. NAADP‐induced Ca 2+ signals mediate a growing number of cellular functions, ranging from proliferation to muscle contraction and differentiation. Recently, NAADP has recently been shown to regulate angiogenesis by promoting endothelial cell growth. It is, however, still unknown whether NAADP stimulates proliferation also in endothelial progenitor cells, which are mobilized in circulation after an ischemic insult to induce tissue revascularization. Herein, we described a novel approach to prepare NAADP‐containing liposomes, which are highly cell membrane permeable and are therefore amenable for stimulating cell activity. Accordingly, NAADP‐containing liposomes evoked an increase in intracellular Ca 2+ concentration, which was inhibited by NED‐19, a selective inhibitor of NAADP‐induced Ca 2+ release. Furthermore, NAADP‐containing liposomes promoted EPC proliferation, a process which was inhibited by NED‐19 and BAPTA, a membrane permeable intracellular Ca 2+ buffer. Therefore, NAADP‐containing liposomes stand out as a promising tool to promote revascularization of hypoxic/ischemic tissues by favoring EPC proliferation. J. Cell. Biochem. 118: 3722–3729, 2017. © 2017 Wiley Periodicals, Inc. Abstract : NAADP‐containing liposomes have been prepared by diluting NAADP with either KCl (KL) or PBS (PL). KL formulations did not change intracellular Ca 2+ levels, while PL did. NAADP‐containing liposomes released Ca 2+ from two pore channels and were, therefore, able to stimulate EPC proliferation.